Gaspereau Fishing on the Southwest Margaree: Gathering at the River - Beaton, Elizabeth (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract For generations, farming families on the Southwest Margaree River in Cape Breton have harvested gaspereau, the fish also known as alewife. The Margaree gaspereau is sold for lobster bait, or to buyers who export it to the Caribbean, mainly Haiti. In this article, narratives form the basis of understanding the natural, technological, regulatory and commercial processes involved in the gaspereau fishery on the Southwest Margaree River, in particular through storytelling and anecdotes. The gaspereau trap used on the Margaree is of particular interest because it was developed on the Margaree River by a Mi’kmaq fisher; it is now used by both native and non-native gaspereau fishers on Cape Breton Island. The sources for this study consist mainly of interviews with those directly involved in the fishery, and, to a lesser extent, discussions with government officials and the wider Margaree community. The result is a realization that the Margaree gaspereau fishery is important, not only as an income supplement, but also as a form of social cohesion in a particular community.